A orquestra e a vida: percursos juvenis na Orquestra Geração - Lopes, João Teixeira (2018)
Following a sociology of dispositional plurality, to which is added the importance of the design and construction of possibility fields for action, we analyse youth orchestra pathways based on sociological portraits, reconstituting dispositional transfers between contexts and processes of socialization, based on the Generation Orchestra experience, which is a musical project of social inclusion originating in Venezuelan El Sistema. In this way, we intend to rescue the origin of dispositions and the strength of the contexts of their activation (or inhibition), together with its potential transferability to other frameworks for socialization. We conclude with the strong impact of orchestral experience in the formation of new skills and dispositions in uneven degree of intensity depending on the actors , the uniqueness of its pathways and the contexts in which they move.